Catheter ablation reduces ventricular tachycardia burden in patients with arrhythmogenic right ventricular cardiomyopathy: insights from a north-western French multicentre registry. Issue 2 (24th December 2016) - Souissi, Zouheir; Boulé, Stéphane; Hermida, Jean-Sylvain; Doucy, Alexandre; Mabo, Philippe; Pavin, Dominique; Anselme, Frédéric; Auquier, Nathanaël; Ninni, Sandro; Coisne, Augustin; Brigadeau, François; Deken-Delannoy, Valérie; et al.
Abstract: Aims: Studies assessing radiofrequency ablation (RFA) of ventricular tachycardia (VT) in arrhythmogenic right ventricular cardiomyopathy (ARVC) report VT recurrences, but have not evaluated the impact of RFA on relevant clinical events during follow-up. We aimed to investigate relevant RFA outcomes in a multicentric registry. Methods and results: This study included 49 patients with ARVC (46 with definite diagnosis, 3 with borderline diagnosis according to revised Task Force Criteria) who underwent 92 RFA procedures (83 endocardial, 9 combined endo–epicardial) between 1999–2015. Ventricular tachycardia recurrences and VT burden were assessed after each procedure or after the last RFA. Over a mean follow-up of 64 ± 51 months, VT-free survival was 37% at 1 year, 19% at 5 years, and 14% at 10 years. Ventricular tachycardia burden was significantly reduced after one procedure (23 vs. 11 VT episodes/year, P  < 0.01) and after the last RFA (14 vs. 2 VT episodes/year, P  < 0.01). Over a mean follow-up of 49 ± 52 months, clinical response after the last RFA (freedom from sudden cardiac death, VT requiring hospitalization, or heart transplantation) was 86% at 1 year, 69% at 5 years, and 60% at 10 years. Clinical response was associated with right ventricular dysfunction (RVD) and low numbers of mappable VT before the first RFA. Conclusion: RFA was predominantly targeted at the endocardial surface. Ventricular tachycardia recurrences were common, but few ARVC patients experienced major clinical events during follow-up. Further studies should investigate the benefit of extensive substrate ablation combined with endo–epicardial strategies.